Poly(arylene ether nitrile)/lamellar MXene nanosheet composite films fabricated via bio-inspired dopamine surface chemistry. (March 2023) - Dong, Hongyu; Yang, Wei; Sun, Ao; Zhan, Yingqing; Chen, Yiwen; Chen, Ximin
2D lamellar MXene nanosheets have shown the promising candidate for preparing dielectric polymer composites due to their excellent electrical and mechanical properties. However, the high dielectric loss and low temperature resistance restrict their further application, which are still big challenges. In this work, MXene nanosheets were modified by dopamine mediated chemical crosslinking with polyethylenimine, which was further incorporated into the temperature-resistant poly (arylene ether nitrile) (PEN) matrix via a simple solution-casting method to prepare the dielectric MXene/PEN composite film. Specially, the insulating layer originated from polyethylenimine and polydopamine not only enhanced the interface polarization and the uniform dispersion of MXene in the polymer matrix, but also prevented the formation of conductive network. As a result, the MXene/PEN composite film achieved the high dielectric constant of 13.3 (1 kHz) when filling content was 7 wt%, and the dielectric loss was suppressed to 0.042. As the filling content reached 5 wt%, the MXene/PEN composite film had the maximum tensile strength and tensile modulus of 70.9 MPa and 3042.6 MPa, respectively, while maintaining a high elongation at break larger than 6.5%. In addition, the composite film retained the thermal decomposition temperature (T10% ) of 460–521°C and the glass transition temperature higher than 149°C. Therefore, this work provides an alternative way to prepare thermally stable and dielectric polymer composite film with high mechanical strength and low dielectric loss, which is essential to the modern electronic applications.